Herpes Zoster Vaccine Live and Risk of Stroke Among Medicare Beneficiaries: A Population-Based Cohort Study. Issue 5 (20th April 2021) - Yang, Quanhe; Chang, Anping; Tong, Xin; Merritt, Robert
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Herpes zoster (HZ) is associated with increased risk of stroke, and zoster vaccine live (ZVL, Zostavax) reduces the risk of HZ. No study has examined the association between ZVL (Zostavax) and risk of stroke. Present study examined association between receipt of ZVL (Zostavax) and risk of stroke among older US population. Methods: Our study included 1 603 406 US Medicare fee-for-service beneficiaries aged ≥66 years without a history of stroke and who received ZVL (Zostavax) during 2008 to 2014, and 1 603 406 propensity score-matched unvaccinated beneficiaries followed through to December 31, 2017. We used Cox proportional hazard models to examine association between ZVL (Zostavax) and composite fatal or nonfatal incident stroke outcomes. Results: During a median of 5.1 years follow-up (interquartile range, 3.9–6.7), we documented 64 635 stroke events, including 43 954 acute ischemic strokes and 6727 hemorrhagic strokes, among vaccinated beneficiaries during 8 755 331 person-years. The corresponding numbers among unvaccinated beneficiaries were 73 023, 50 476, and 7276, respectively, during 8 517 322 person-years. Incidence comparing vaccinated to unvaccinated beneficiaries were 7.38 versus 8.57 per 1000 person-years for all stroke, 5.00 versus 5.90 for acute ischemic stroke, and 0.76 versus 0.84 for hemorrhagic stroke ( P <0.001 for all difference). Adjusted hazard ratios comparing vaccinated to unvaccinated beneficiaries were 0.84 (95% CI, 0.83–0.85), 0.83 (0.82–0.84), and 0.88 (0.85–0.91) for all stroke, acute ischemic stroke, and hemorrhagic stroke, respectively. The association between ZVL (Zostavax) and risk of stroke appeared to be stronger among younger beneficiaries, beneficiaries who did not take antihypertensive or statin medications and who had fewer comorbid conditions ( P <0.05 for interaction) but largely consistent across sex, low-income status, and racial groups. Conclusions: Among Medicare fee-for-service beneficiaries, receipt of ZVL (Zostavax) was associated with lower incidence of stroke. Our findings may encourage people to get vaccinated against HZ to reduce HZ and HZ-associated stroke risk.